Patterning of Nanoparticle‐Based Aerogels and Xerogels by Inkjet Printing. Issue 39 (8th August 2019) - Lübkemann, Franziska; Miethe, Jan Frederick; Steinbach, Frank; Rusch, Pascal; Schlosser, Anja; Zámbó, Dániel; Heinemeyer, Thea; Natke, Dominik; Zok, Dorian; Dorfs, Dirk; Bigall, Nadja C.
Abstract: Nanoparticle‐based voluminous 3D networks with low densities are a unique class of materials and are commonly known as aerogels. Due to the high surface‐to‐volume ratio, aerogels and xerogels might be suitable materials for applications in different fields, e.g. photocatalysis, catalysis, or sensing. One major difficulty in the handling of nanoparticle‐based aerogels and xerogels is the defined patterning of these structures on different substrates and surfaces. The automated manufacturing of nanoparticle‐based aerogel‐ or xerogel‐coated electrodes can easily be realized via inkjet printing. The main focus of this work is the implementation of the standard nanoparticle‐based gelation process in a commercial inkjet printing system. By simultaneously printing semiconductor nanoparticles and a destabilization agent, a 3D network on a conducting and transparent surface is obtained. First spectro‐electrochemical measurements are recorded to investigate the charge–carrier mobility within these 3D semiconductor‐based xerogel networks. Abstract : Semiconductor nanoparticle‐based aerogel‐coated electrodes are manufactured automatically via inkjet printing. By simultaneously printing a destabilization agent and semiconductor nanoparticles, a 3D aerogel‐type network on a conducting and transparent surface is obtained. Furthermore, the charge‐carrier mobility within the 3D aerogel‐type network is investigated via spectro‐electrochemical measurements.